THE EMERGENCE OF CLASSES AND THE FORMATION OF FEUDAL STATES IN KOGURYO, PEKCHE, SILLA. - Madaminov Tulqinjon Mamayunusovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In this article, instead of the Korean state, the formation, lifestyle, religion, and culture of the ancient Goguryeo, Paekche, and Silla feudal states are fully explained.